Vibration analyses of single scull oars - Breitschädel, F.; Loset, S. (Procedia Engineering, 2010)
Numerous parameters contribute to rowing performance. Selecting the right oars can therefore be an important factor for success. This paper describes laboratory experiments to aid in the selection of oars. The dynamic properties of 71 oars were measured and compared with the favourite pair of oars from a Norwegian single scull rower. Free oscillation was investigated through eight acceleration sensors placed along the shaft of each oar. The sculls displayed a wide range of dynamic properties, which, when measured, allowed the selection of new oars with damping characteristics similar to the reference pair, but with a significantly lower weight and higher natural frequency. These vibration analyses provide a valuable non-destructive method for testing and selecting personalized oars for top athletes.